Optimalisasi Manajemen Pelayanan Gerai Sehat di Layanan Kesehatan Cuma-Cuma (LKC) Dompet Dhuafa Jawa Tengah - Hadi, Rahmini; Hidayatulah, Aditya (Mabsya: Jurnal Manajemen Bisnis Syariah, 2023)
Free Health Service (LKC) Dompet Dhuafa Central Java is a health program that provides free health services for underprivileged communities. However, to ensure optimal service, it is necessary to optimize the service management of healthy outlets at LKC. The purpose of this study is to identify factors that influence the optimization of healthy outlet service management in LKC and design a theoretical framework that can help in improving the quality of health services in LKC. This study used a qualitative approach with data collection techniques through in-depth interviews. The results showed that the factors that affect the optimization of healthy outlet service management at LKC include: human resource management, drug and medical device procurement management, data management, and community relations management. From the results of the analysis, a theoretical framework was designed which includes six components, namely: planning, organizing, procurement, implementation, supervision, and assessment. This theoretical framework can help in improving the quality of health services in LKC by providing systematic and comprehensive guidance for LKC management. In conclusion, optimization of healthy outlet service management at LKC needs to be carried out continuously to improve the quality of health services. The theoretical framework designed can be used as a reference for LKC management in improving and developing health programs for underprivileged communities.